Becoming a Diplômé in Kinshasa. Education at the Intersection of Politics and Urban Livelihoods - Pype, Katrien (Diversité urbaine)

(untitled) (Groupe de recherche diversité urbaine, 2015)
Like other cities around the globe where the state organizes exams, Kinshasa’s exétat shows the degree to which social difference and urban livelihood are intimately connected. However, despite the assumption that diplômés master book knowledge, recent changes in the practice of the exétat have transformed the meaning of a diplômé, turning that figure into a yankee, i.e., someone who possesses street knowledge that comes from experience with the informal and the illegal. More abstractly, the identity of a diplômé has become a signifier for the opposite of its taken-for-granted signified. Kinois society publicly acclaims the social and cultural capital attached to school degrees; however, most recent diplômés have obtained their degree through bribes and organized cheating.